2023
DOI: 10.1098/rsos.221386
|View full text |Cite
|
Sign up to set email alerts
|

Does artificial feeding impact neonate growth rates in a large free-ranging mammal?

Abstract: Variation and disparity in resource access between individuals in an animal population within human-dominated landscapes require attention as artificial selection processes may be at work. Independent, recreational human–wildlife feeding interactions constitute an increasingly prevalent, yet understudied, food resource for birds and mammals living in our cities. However, only a limited number of risk-taking individuals may access it. Using urban fallow deer as our model species, we hypothesized that if these i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 71 publications
1
13
0
Order By: Relevance
“…Previous studies have shown that extractive activities like hunting and fishing are pushing selection towards less desirable traits in wild animals [64]. Based on our bedsite selection findings coupled with previous findings of increased fawn birth weights and growth rates [7,32,48], consistent beggar mothers seem to have higher reproductive success than their conspecifics that beg less. It could be argued that feeding activities promote the artificial selection of bolder begging behaviours [7,12].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Previous studies have shown that extractive activities like hunting and fishing are pushing selection towards less desirable traits in wild animals [64]. Based on our bedsite selection findings coupled with previous findings of increased fawn birth weights and growth rates [7,32,48], consistent beggar mothers seem to have higher reproductive success than their conspecifics that beg less. It could be argued that feeding activities promote the artificial selection of bolder begging behaviours [7,12].…”
Section: Discussionsupporting
confidence: 76%
“…Previous research has also shown that prolonged nursing occurs in heavier offspring in other ungulates [62]. Combining these early-life characteristics of higher birth weight and faster growth rates [7,32,48] with our findings about bedsite characteristics (low visibility) and location (more distant from humans and their dogs compared with the other females in this population) [34], the offspring of bolder mothers are consistently awarded multiple survival advantages (to be further explored by future research) from in utero to young adult life stages. This provides evidence that begging mothers are better adapted to this environment than shyer females.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…an objective proxy for age sensu Amin et al (2021), determined by placing the fawn into a 100-litre bag, which was weighed using a digital scale – resolution: 0.01 kg, Dario Markenartikelvertrieb); GPS coordinates of the bedsite (using a Garmin etrex 30 hand-held unit); and bedsite visibility (see below for full description). Fawns were routinely recaptured to monitor body growth (Griffin et al, 2023), allowing us to collect bedsite characteristics in older fawns. Our final database consisted of fawn capture data collected in 2018 (n = 102 individual fawns), 2019 (n = 81), and 2020 (n = 100).…”
Section: Methodsmentioning
confidence: 99%
“…If engagement with feeding interactions is not random, and instead is driven by behavioral type, then they may also only be occurring in a subset of the population. Recent studies have indicated that independent feeding of wildlife can impact the weight and growth rates of offspring (Griffin, Haigh, et al, 2023; Griffin, Haigh, Amin, et al, 2022) (Figure 2) and that the resultingly larger neonates have increased survival rates (Amin et al, 2022). This highlights the potential that artificial selection may be at work and we may involuntarily be manipulating wild populations.…”
Section: Current Knowledge Gapsmentioning
confidence: 99%